Urinary infection in patients with type 2 diabetes mellitus: frequency, etiology, antimicrobial susceptibility and risk factors - Elsa Lucas-Parrales; Cristobal Franco; Maribel Castellano-González (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2018)
Urinary infection is common in diabetic patients. The objective of this research was to determine the frequency, etiology, antimicrobial susceptibility and risk factors associated with urinary tract infection in patients with type 2 diabetes. 108 outpatients with a presumptive diagnosis of urinary tract infection during May 2016-May 2017, in the city of Jipijapa, Ecuador, were studied. For the uroculture the calibrated loop technique was used. The susceptibility to antibiotics was determined by the Kirby & Bauer method. The qualitative variables were compared with chi-squared or Fisher's exact test. The Odd radio (OR) and its 95% confidence intervals (CI) were calculated. Values of p ≤ 0.05 were considered significant. A frequency of 73.15% of urinary infection was found. The microorganism most frequently isolated was Escherichia coli (78.48%). The highest percentages of resistance were observed for amoxicillin (78.87%) and cephalexin (71.83%). Bad hygiene habits, the presence of kidney stones and an active sex life were risk factors for urinary tract infections. Nitrofurantoin, fosfomycin, fluoroquinolones and some beta-lactams still represent a useful alternative in the chemotherapy of uncomplicated urinary tract infections in diabetic patients.